The Long Night : Readings and Stories to Help You through Depression. - Kantrowitz, Jessica (Fortress Press, 2020)
When you're in the midst of terrible depression, the days and weeks can feel like an eternity. Drawing on the wisdom of spiritual figures from the past and present--including Henri Nouwen, Thomas Merton, and many others--The Long Night is a comforting and inspirational companion. Ordained minister, writer, and artist Jessica Kantrowitz has been where you are. As a mentor and friend, she will walk with you on this journey toward life and light.